Food Choice Mimicry on a Large University Campus - Gligorić, Kristina; Chiolero, A.; Kiciman, Emre; White, Ryen W.; Horvitz, Eric; West, R. (PNAS Nexus, 2024)
Social influence is a strong determinant of food consumption, which in turn influences the environment and health. Purchasing mimicry, a phenomenon where a person copies another person’s purchases, has been identified as the key governing mechanism. Although consistent observations have been made on the role of purchasing mimicry in driving similarities in food consumption, much less is known about the precise prevalence, the affected subpopulations, and the food types most strongly associated with mimicry effects. Here, we study social influence on food choice through carefully designed causal analyses, leveraging the sequential nature of shop queues on a large university campus. In particular, we consider a large number of adjacent purchases where a focal user immediately follows another user (“partner”) in the checkout queue and both make a purchase. Across food additions purchased during lunchtime together with a meal, we find that the focal user is significantly more likely to purchase the food item when the partner buys the item, vs. when the partner does not, increasing the purchasing probability by 14% in absolute terms, or by 83% in relative terms. The effect is observed across all food types, but largest for condiments. Furthermore, purchasing mimicry is present across age, gender, and status subpopulations, but strongest for students and the youngest. We elucidate the behavioral mechanism of purchasing mimicry, and derive direct implications for interventions improving dietary behaviors on campus, such as facilitating preordering to reduce detrimental interactions.